2022
DOI: 10.1177/18632521221133812
|View full text |Cite
|
Sign up to set email alerts
|

Building better pediatric surgeons: A sentiment analysis of online physician review websites

Abstract: Purpose: Physician review websites are a heavily utilized patient tool for finding, rating, and reviewing surgeons. Natural language processing such as sentiment analysis provides a comprehensive approach to better understand the nuances of patient perception. This study utilizes sentiment analysis to examine how specific patient sentiments correspond to positive and negative experiences in online reviews of pediatric orthopedic surgeons. Methods: The online written reviews and star ratings of pediatric surgeo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Similar concepts have been noted in previous reports in which patients have rated physicians higher online if they perceived them to have good communication skills [30]. For example, Butler et al showed that pediatric surgeons who communicated effectively were more likely to receive higher online ratings and more positive comments [24]. All caregivers in this study felt that providers communicated the next steps in their child's care, which ultimately makes caregivers more comfortable with their children's providers.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Similar concepts have been noted in previous reports in which patients have rated physicians higher online if they perceived them to have good communication skills [30]. For example, Butler et al showed that pediatric surgeons who communicated effectively were more likely to receive higher online ratings and more positive comments [24]. All caregivers in this study felt that providers communicated the next steps in their child's care, which ultimately makes caregivers more comfortable with their children's providers.…”
Section: Discussionsupporting
confidence: 85%
“…Further, convenience is largely associated with satisfaction. Previous literature has shown that both convenience and office environmental factors influence patient and caregiver perspectives when they critique healthcare settings [24][25][26]. In a similar manner, Allshouse et al articulated that many primary care settings are unable to meet the clinical needs of CMC alone [16].…”
Section: Discussionmentioning
confidence: 99%
“…VADER has been previously utilized in studies investigating the emotional tone of comments on online social media platforms such as Reddit, 6 Twitter, 7 , 8 and in healthcare on PRW to evaluate patient reviews. 3 , 4 , 9 Within ophthalmology, VADER analysis of PRWs, such as Healthgrades, has identified overall positive sentiment among patients, with specific concerns surrounding wait times and staff for pediatric ophthalmology and glaucoma providers. 4 , 5 …”
Section: Introductionmentioning
confidence: 99%